Perancangan Sistem Pelaporan Absensi Asrama Melalui Whatsapp - Elmor Benedict Wagiu; Edrick Christian Warasiwa (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2020)
Technology of information and communication currently touches many aspects of daily human life. With the development of technology, many activities have become easier to use, record and report. Universitas Advent Indonesia is an educational institution that uses information systems for record and report in many ways, one of them is record and report of attendance activities in the dormitory. This information system can be accessed by students and also by parents/guardians. However, parents/guardians of students want to be able to access the information. Therefore the objectives of this study are (1) facilitating the delivery of attendance information to parents/guardians of inside students (2) to make efficient use of paper, and (3) eliminating distance constraints in information transmission. The conclusions of this study are (1) WhatsApp can be used for deliver the report of dormitory attendance and makes the Head of the Dormitory easier to send student attendance information to parents/guardians, (2) System provides convenience in send real-time information.